داغ وامیر: رام پور میں - Ali, Dr. Liaquat (Zoraiz, 2022)
In this paper, the relation of Dagh and Ameer with Ram Pur has been elaborated. Dagh Dehlvi and Ameer Minai migrated to Ram Pur from their native cities. There was a healthy competition among these popular poets in the state. Both were employees and had a great time at the peaceful place. Ram Pur was the place where the hidden qualities of both the leading poets were revealed. In their earlier works at their schools, i.e. Delhi and Lucknow respectively. A drastic change can be witnessed in their verses written at Ram Pur. So we can say That Dagh and Ameer were influenced by the literary environment of Ram Pur and contributed a lot in making the place a 3rd school of poetry alongside Delhi and Lucknow as well.